Out there - Taylor, Alex (Proceedings of the 2011 annual conference on Human factors in computing systems, CHI '11, 2011)
Alex S Taylor (2011) Out There, CHI '11, p. 685-694, New York, NY: ACM Press "Out there" is increasingly becoming a topic of concern in HCI. Thanks to various clarion calls, researchers in the field are turning their attention to technology-mediated activities that are shaped less by Euro-American sensibilities and defined more by how they are culturally and geographically distinct. Fieldwork and ethnography researchers, for instance, are beginning to investigate ICT use at religious and spiritual sites, by the socially excluded and disenfranchised, and by people in developing regions. In this paper, I concentrate on the latter focus on development to reflect on HCI's disciplinary turn "out there". Specifically, I take the following three themes as common rhetorical devices in such work: (i) the network, (ii) difference and (iii) complexity. Through examples, I discuss how each of these themes has been mobilised. I then use materials from anthropology, science and technology studies, and to a lesser extent geography and postcolonial studies to complicate and in some cases question the interpretative frames that are being applied. Thus, my hope is that this paper is seen as a thought piece that deepens our thinking around HCI's efforts to look "out there" by paying critical attention to what is going on "in here".